Synthesis and Characterization of Bi2TixV1-xO5.5-δ as Electrolyte Material in Solid Oxide Fuel Cell - Bambang Prijamboedi; Citra Deliana Dewi Sundari; Rolan Rusli; Ismunandar Ismunandar (Indonesian Journal of Physics, 2011)
Oxide materials of Bi2TixV1-xO5,5-δ have been synthesized by means of conventional solid state reaction method. Substitution of Ti atom for the V sites leads to the formation of single phase Bi2TixV1-xO5,5-δ material with I4/mmm space group of tetragonal structure as well as gives results in large grain size and good sinterability of the ceramic material. With Ti concentration of x = 0.2, sample without the presence of porous could be obtained. The ionic conductivity of Bi2TixV1-xO5,5-δ increases significantly with the presence of Ti atoms. This Ti substitution also reduces phase transition temperatures in Bi2TixV1-xO5,5-δ materials. The conductivity data and scanning electron microscope images show that the Ti concentration in Bi2TixV1-xO5,5-δ could be applied as much as x = 0.2, which is higher than reported before and it still gives better properties.